2015
DOI: 10.1111/apt.13361
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early thiopurines on surgery in 2770 children and young people diagnosed with inflammatory bowel disease: a national population-based study

Abstract: SUMMARY BackgroundThe role of early thiopurine treatment in inflammatory bowel disease (IBD) is unproven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…4 We would be interested to know if Safroneeva et al analysed their data set to assess the impact of duration of therapy and adjusted for this variable in their analysis of the impact of early therapy on surgical outcomes? In our most recent study, we reported the benefit of early immunomodulator therapy in reducing the risk of surgery in children and young adults, 5 akin to the findings of Markowitz et al 6 Were the authors able to identify a differential effect of IMs between younger and older onset CD in their cohort? Our recent findings support the notion that patients presenting with CD at a young age are more likely to gain benefit from early immunomodulator usage, with an associated reduced surgical risk.…”
mentioning
confidence: 74%
“…4 We would be interested to know if Safroneeva et al analysed their data set to assess the impact of duration of therapy and adjusted for this variable in their analysis of the impact of early therapy on surgical outcomes? In our most recent study, we reported the benefit of early immunomodulator therapy in reducing the risk of surgery in children and young adults, 5 akin to the findings of Markowitz et al 6 Were the authors able to identify a differential effect of IMs between younger and older onset CD in their cohort? Our recent findings support the notion that patients presenting with CD at a young age are more likely to gain benefit from early immunomodulator usage, with an associated reduced surgical risk.…”
mentioning
confidence: 74%
“…Our study showed that independent risk factors associated with SR were penetrating disease behavior, ileocolonic disease location, and isolated upper GI disease location. However, the use of TPs was an independent protective factor of SR. Several studies indicated that TPs could prevent and reduce the incidence of the first intestinal resection of CD patients . A meta‐analysis including 17 retrospective observational studies demonstrated that the use of TPs could reduce the risk of first bowel resection by 40% in CD patients .…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of TPs was an independent protective factor of SR. Several studies indicated that TPs could prevent and reduce the incidence of the first intestinal resection of CD patients. 21,22 A meta-analysis including 17 retrospective observational studies demonstrated that the use of TPs could reduce the risk of first bowel resection by 40% in CD patients. 23 However, few studies focused on the effect of postoperative TPs therapy on SR as the primary outcome among CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously published detailed methodologies in defining incident cases of inflammatory bowel disease from the CPRD. 29,30,31,32,33 In brief, to separate prevalent from incident cases of CD, we identified patients with a first Read code for CD at least one year after registering with a 'Up To Standard' practice for the period January 1st 2005 to December 31st 2014.…”
Section: Incident Case Definition and Cohort Constructionmentioning
confidence: 99%
“…This was defined as the first intestinal surgical procedure coded for following diagnosis of CD, and was derived using Read/OXMIS codes for intestinal surgery as previously described. 29,31…”
Section: Outcome Measuresmentioning
confidence: 99%